2007
DOI: 10.1044/1092-4388(2007/101)
|View full text |Cite
|
Sign up to set email alerts
|

A Perceptual Correlate of the Labial-Coronal Effect

Abstract: Conclusion: This study demonstrates that the Labial-Coronal effect also occurs in the course of on-line speech processing. This result is interpreted in relation with theories assuming a link between perception and action in the human speech processing system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 49 publications
5
35
0
Order By: Relevance
“…In this context, Tsuji et al (2012) explored Japanese adults' production and perception of plosive sequences containing a labial consonant (/p/ or /b/) and a coronal consonant (/t/ or /d/). The results revealed that Japanese adults have an LC bias in production, supporting the explanations in terms of articulatory constraints (MacNeilage & Davis, 2000a;MacNeilage et al, 2000;Sato et al, 2007). However, Japanese adults did show a perceptual CL bias for these plosive sequences, showing the influence of language exposure on perceptual biases as had been previously suggested (Nazzi et al, 2009;Gonzalez-Gomez & Nazzi, 2012a,b,c).…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…In this context, Tsuji et al (2012) explored Japanese adults' production and perception of plosive sequences containing a labial consonant (/p/ or /b/) and a coronal consonant (/t/ or /d/). The results revealed that Japanese adults have an LC bias in production, supporting the explanations in terms of articulatory constraints (MacNeilage & Davis, 2000a;MacNeilage et al, 2000;Sato et al, 2007). However, Japanese adults did show a perceptual CL bias for these plosive sequences, showing the influence of language exposure on perceptual biases as had been previously suggested (Nazzi et al, 2009;Gonzalez-Gomez & Nazzi, 2012a,b,c).…”
Section: Introductionsupporting
confidence: 84%
“…Classically, the effect has been explained as the result of production constraints (Ingram, 1974;MacNeilage & Davis, 2000a;MacNeilage et al, 2000;Sato et al, 2007). In contrast, Nazzi et al (2009) and Gonzalez-Gomez and Nazzi (2012a) offered a perceptual explanation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations